Proteomics of follicular fluid from buffaloes (Bubalus bubalis): Unraveling the secrets of follicular development - Marques, Nayara Fernanda Silva [UNESP]; Codognoto, Viviane Maria [UNESP]; Souza, Fabiana Ferreira de [UNESP]; Scott, Caroline [UNESP]; Janini, Ludimila Cardoso Zoccal [UNESP]; Brochine, Suzane [UNESP]; Tironi, Stella Maris Teobaldo [UNESP]; Camargo, Laíza Sartori de [UNESP]; Alvarez, Marcus Vinicius Niz [UNESP]; Oba, Eunice [UNESP] (Elsevier, 2022)
The objective of this study was to identify, quantify, and describe the proteome of follicular fluid according to morphometry of ovarian follicles from buffaloes. Follicular fluid was collected from 112 ovaries from a slaughterhouse. The samples were separated into 6 groups, 〈 5 mm, 5 – 8 mm, or 〉 8 mm follicles in ovaries with or without corpus luteum. An aliquot containing 50 µg was used for tryptic digestion and mass spectrometry (nano-LC ESI-Q-TOF MS/MS) based on the total protein concentration. Multivariate statistical analysis was performed, based on the principal component analysis (PCA), partial least squares-discriminant analysis (PLS-DA) represented by variable importance in projection (VIP) score, dendrogram, and gene ontology (biological process). Seven proteins presented an α > 1.5 VIP score. Lysosomal alpha-glucosidase and serine protease inhibitor clade E member 2 (without corpus luteum) showed higher abundance in the large follicles (5 - 8 mm and > 8 mm); haptoglobin, histone H2A type 1, histone H2B, glutathione S-transferase A1 (with corpus luteum), and serine protease inhibitor clade E member 2 (with corpus luteum) showed higher abundance in the small follicles (< 5 mm); and mucin 19 in the follicles from ovaries with corpus luteum. The physiology of follicular development in this species is still unclear, then we believe these results may improve studies with in vitro oocyte maturation for embryo production since the proteins found in greater abundance in all groups are mostly related to follicular growth and development and oocyte maturation.
Keywords: Buffalo; Corpus luteum; Follicle-liquid; Follicular-development; Protein